EROSION CONTROL OF SOILS USING SOME GEOTEXTILE MATERIALS (International Journal of Food and Nutritional Sciences, 2022)
Running water, waves, wind, moving ice, or other earth science sheet and bank erosion forces can all cause soil or rock debris to become untangled, disconnected, and transferred from one location to another, causing erosion. Underneath stone riprap, geotextiles are a good and affordable alternative to conventional hierarchic filters. The material of the duvet may shift as a result of wave action or currents, which could lead to abrasion. Durability, dimensional stability, and resistance to tearing, puncture, and burst are the strength attributes that are typically considered to be of the utmost importance. It makes sense to build the silt fence in the shape of a horseshoe over a level area. This contributes to the runoff ponding and will improve the strength.